EFEKTIVITAS PELAKSANAAN MUTASI TENAGA KERJA PADA PT NATIONAL SAGO PRIMA (NSP) DI KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - Nazri Nazri; Firdaus Firdaus; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
A muttion is a change of position, a title, a place of work done bot horizontally and vertically in an organization. Transfers are a common thing for companies that have branch offices in several regions and transfers are part of the personnel management policy to distribute human resources appropriately and according to the company’s needs. However, transfers need to pay attention to law Number 13 of 2003 concerning Manpower, company regulations, and work agremeents so that there are no diputes between workers and employer such as the dispute between PT National Sago Prima and 9 (nine) workers of PT National Sago Prima.The purpose of the study was to determine the effectiveness of labor transfer by PT National Sago Prima based on Law Number 13 of 2003 concerning Employment and the determine the efforts and resolution of labor transfer problem wit PT National Sago Prima. This type of research is sociological yuridis, this research is descriptive analytic. The location of this research is PT National Sago Prima, Tebing Tinggi Timur district, Meranti Island Regency. The sources of data used are primary data, secondary data and tertiary data. Data collection techniques with interview and literature reviews.From the result of this study, it is concluded that first, the implementation of mutations carried out by PT National Sago Prima is in accordance with the provisions of Law Number 13 of 2003 concerning Employment and company regulation, but is implementation has not been effective due to the education factor of workers being transferred is still law and impressed second, efforts to resolve disputes between workers and PT National Sago Prima have reached an agreement that 9 (nine) workers have been laid off bassed on article 161 Paragraf 1 law Number 13 of 2003 concerning Manpower.Keywords: Mutation - Labor - At PT National Sago Prima